A qualitative study of factors influencing different generations of Newfoundland and Saskatchewan trained physicians to leave a work location - Mathews Maria; Seguin Maureen; Chowdhury Nurun; Card Robert T (Human Resources for Health, 2012)
Abstract Background Some studies have suggested that young physicians may have different expectations and practice behaviours than their older generational counterparts, including their reasons for wanting to remain or leave a community. This study examined the factors associated with a physician’s decision to leave a work location. We compared different generations of physicians to assess whether these factors have changed over generations. Methods We conducted semi-structured, qualitative interviews with 48 physicians who graduated from two Canadian medical schools. We asked each physician about the number and nature of work location changes and the factors related to their decisions to leave each location. Interview transcripts and notes were analysed using a thematic analysis approach. Results Dissatisfaction with the working environment was the most frequently cited reason for leaving a location for physicians of all generations. Elements which contributed to the quality of the work environment included the collaborative nature of the practice, the relationship with administrators, and access to resources and personnel. For younger physicians, the work environment had to meet their personal expectations for work-life balance. While remuneration level was given by some physicians as the key reason for leaving a location, for others it was the “last straw” if the work environment was poor. A small number of older generation physicians moved in response to political events and/or policies Conclusions We documented generational differences in physicians’ reasons for choosing a work location. We found that a poor work environment was universally the most important reason why a physician chose to leave a location. A few physicians who were unsatisfied with their work location identified level of remuneration as an additional reason for leaving. Some older generation physicians cited political climate as a reason for leaving a work location. While economic factors have largely been the focus of recruitment and ...